Improving the Basic Writing Skills of Second-Grade Students in Class II C at SDN 30 Mattirowalie Through a Picture-Based Learning Method Using Canva - Jein Tita Jein Tita; Muhammad Hasby Muhammad Hasby; Reski Pilu Reski Pilu (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to determine whether a picture-based learning method using Canva can improve the basic writing skills of second-grade students in Class II-C at SDN 30 Mattirowalie. This study employed a quantitative approach with a pre-experimental one-group pretest-posttest design. The population and sample consisted of all 27 students in Class II-C at SDN 30 Mattirowalie, selected using total sampling. Data were collected using a basic writing skills test and analyzed using descriptive statistics, the Shapiro–Wilk normality test, a paired-samples t-test, and the N-Gain test. The results indicate that the picture-based learning method using Canva significantly improved students' basic writing skills. This is evidenced by an increase in the mean score from 52.81 on the pretest to 76.52 on the posttest, an increase of 23.71 points. The percentage of students achieving the learning mastery criterion increased from 22.22% to 92.60%, while the standard deviation decreased from 14.51 to 8.62, indicating greater consistency in students’ writing performance. Furthermore, the paired-samples t-test yielded a significance value of 0.000 (Sig. (2-tailed) < 0.05), leading to the rejection of H0 and the acceptance of Ha. In addition, the N-Gain test produced an average score of 0.50, categorized as moderate.